ONLINE GAMING BAHAVIOR AMONG JUNIOR HIGH SCHOOL STUDENTS: THE ROLE OF PARENTAL CONTROL, FEAR OF MISSING OUT (FOMO), AND SELF-CONTROL: Perilaku Bermain Game Online pada Siswa SMP: Peran Kontrol Orang Tua, Fear of Missing Out (FOMO), dan Kontrol Diri - Amalia Faron, Bekti; Hastuti, Dwi (Jurnal Ilmu Keluarga dan Konsumen, 2024)
This fast-paced digitalization era has made online gaming as one of internet content that often accessed by adolescent. This study aims to analyze the influence of parental control, FOMO, and self-control towards adolescents’ online gaming behavior. For about 200 of 7th grade students from one of selected junior high school in Banyumas Regency were participated in this study. The location and sample of this study were chosen using purposive sampling technique by criteria students aged 12-14years and come from intact family. Data were collected by self-report through filling out a questionnaire. Majority of adolescents had parental control practice and self-control in moderate level, while FOMO and online gaming behavior were categorized in low level. Boys and girls were reported to have significant difference of self-control and online gaming behavior. Boys were discovered to have a higher level of self-control and online gaming behavior than girls. It also discovered that parental control and FOMO significantly influence the level of self-control. This self-control finally influences the level of adolescent’s online gaming behavior. Parents should understand how important their role is to prevent online gaming addiction among adolescents.